On REIPPPP: Exploring the potential of intermediaries to support the implementation of the programme's socio-economic development obligations in low-income communities - Mgxashe, Phumeza (Graduate School of Business (GSB), 2022)
This research explores the potential role of intermediaries in the implementation of socioeconomic development (SED) benefits through the Renewable Energy Independent Power Producer Programme (REIPPPP) in low-income communities. SED benefits are a procurement requirement that forms part of REIPPPP's Economic Development scorecard and are required to be implemented in identified beneficiary communities, with the aim of improving livelihoods in such communities. Literature points to the fact that, community development is not a function of the private sector and that intermediaries can have success in partnering with communities in their quest for development. This research is approached through a qualitative inductive study of a case study. The case study is Project90by2030, a not-for-profit organisation (NPO) and public benefit organisation (PBO) that is focused on the mobilisation of and advocacy for clean energy in energy poor lowincome communities. The research pays attention to the organisation's community development approach and what possible learning benefits there could be for the REIPPPP. Interviews were held with community participants and facilitators of the Community Partnership Programme of the organisation. The research finds that low-income communities experience exclusion and inequality and identifies the agents of the said exclusion and inequality. This thesis argues that intermediaries can play an important role to bridge inequality of agency and other power dynamics that work to the detriment of the empowerment of low-income communities. It concludes that socio-economic community development is a contribution to society that business should pursue, with the support of intermediaries and with local government as a key strategic partner.